Battery monomer, battery and electric device
Patent Information
- Application Number
- CN202380060953.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-17
- Publication Date
- 2025-04-01
AI Technical Summary
The reliability and cycle performance of the battery cells are poor, mainly because the free electrolyte is squeezed out, causing the positive and negative electrodes to be short-circuited, which increases the risk of dendrite formation.
The lyophilic polymer is introduced into the electrode assembly of the battery cell to form a condensed electrolyte with the free electrolyte, reducing the presence of free electrolyte, reducing the risk of dendrite formation, and improving the conductivity of the electrolyte.
By reducing the risk of extrusion of free electrolyte, the reliability and cycle performance of battery cells are improved, and the electrical performance of the battery is significantly improved.
Smart Images

Figure CN119744461A_ABST
Abstract
Description
Battery cells, batteries and electrical devices Technical Field
[0001] The present application relates to the field of batteries, and in particular to a battery cell, a battery, and an electrical device. Background Art
[0002] Battery cells have the characteristics of high capacity and long life, and are therefore widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric airplanes, electric boats, electric toy cars, electric toy boats, electric toy airplanes and power tools, etc.
[0003] As battery applications become increasingly widespread, the requirements for battery cell performance are becoming increasingly stringent. To improve battery cell performance, optimization and improvement are often performed on the battery cells; however, the reliability and cycle performance of battery cells remain poor.
[0004] Summary of the Invention
[0005] The present application is made in view of the above-mentioned problems, and its object is to provide a battery cell, a battery, and an electric device.
[0006] A first aspect of the present application provides a battery cell, comprising an electrode assembly and an electrolyte, wherein the electrode assembly comprises a first electrode piece, a second electrode piece, and a separator, wherein the first electrode piece and the second electrode piece have opposite polarities, and the separator is disposed between the first electrode piece and the second electrode piece, and at least one of the first electrode piece, the second electrode piece, and the separator comprises a lyophilic polymer; and the battery cell satisfies the following formula:
[0007] y represents the mass of free electrolyte in the battery cell, and its unit is g;
[0008] M represents the mass of the battery cell before drying, and its unit is g;
[0009] M' represents the mass of the battery cell after drying, and its unit is g.
[0010] Therefore, when the embodiment of the present application satisfies the above formula range, the lyophilic polymer and the electrolyte have good affinity, and the electrolyte can quickly diffuse between the molecular chains of the lyophilic polymer and be wrapped by the molecular chains. After swelling, adsorption, polymerization and coagulation, an elastic porous slow-release electrolyte is obtained. The slow-release electrolyte can absorb the free electrolyte in the battery cell and reduce the presence of free electrolyte. Since the free electrolyte is locked, the risk of the free electrolyte being squeezed out is reduced, thereby reducing the risk of short-circuiting the positive and negative electrode plates due to dendrite formation, and improving the reliability and cycle performance of the battery cell. In addition, the absorbed free electrolyte forms a new condensed electrolyte with the elastic porous slow-release electrolyte, which can ensure that the electrolyte has a high electrical conductivity, thereby improving the electrical performance of the battery cell.
[0011] In some embodiments, the battery cell satisfies the following formula:
[0012] Optionally,
[0013] Therefore, in the case of the above formula in the embodiment of the present application, it is possible to further improve both the reliability and cycle performance of the battery cell.
[0014] In some embodiments, the battery cell further satisfies the following formula:
[0015] and / or
[0016] m1 represents the mass of the electrode assembly before drying, and its unit is g;
[0017] m2 represents the mass of the electrode assembly after drying, and its unit is g.
[0018] Therefore, in the case of the above formula in the embodiment of the present application, it is possible to further improve both the reliability and cycle performance of the battery cell.
[0019] In some embodiments, the amount of free electrolyte per unit capacity of the battery cell is b, with the unit being mg / Ah, 0≤b≤1400; optionally, 0.1≤b≤1000; further optionally, 0.3≤b≤800.
[0020] Therefore, in the case of the above formula in the embodiment of the present application, it is possible to further improve both the reliability and cycle performance of the battery cell.
[0021] In some embodiments, the first electrode includes a current collector and an active material layer arranged on at least one surface of the current collector, the active material layer includes a lyophilic polymer and active material particles; the lyophilic polymer is distributed on the surface of the active material particles; and / or there are multiple active material particles, there are pores between two adjacent active material particles, and the lyophilic polymer is distributed in the pores between the active material particles.
[0022] Therefore, in the embodiment of the present application, the lyophilic polymer is disposed on the first electrode, which can improve the liquid retention capacity of the first electrode and further improve the reliability and cycle performance of the battery cell.
[0023] In some embodiments, the isolation membrane includes a substrate and a coating disposed on at least one surface of the substrate; the lyophilic polymer is distributed in the pores of the substrate; and / or the lyophilic polymer is distributed in the coating; and / or the lyophilic polymer is disposed on the surface of the coating facing away from the substrate.
[0024] Therefore, in the embodiment of the present application, the lyophilic polymer is disposed on the separator, which can improve the liquid retention capacity of the separator and further improve the reliability and cycle performance of the battery cell.
[0025] In some embodiments, the battery cell further includes a liquid electrolyte, wherein the liquid electrolyte is located within the electrode assembly.
[0026] Liquid electrolytes have fluidity, making it easier for them to flow around the active material particles, thereby increasing the transmission rate of active ions. In related technologies, liquid electrolytes generally have the following forms within battery cells: one is diffusion into the pore structure of the electrode assembly, such as being located in the pores of the pole piece and / or the separator; the other is free within the battery cell. The liquid electrolytes of the embodiments of the present application have the following forms: one is diffusion into the pore structure of the electrode assembly, such as being located in the pores of the pole piece and / or the separator; the other is diffusion into the swollen polymer, so that the liquid electrolytes of the embodiments of the present application are basically all located inside the electrode assembly, and there is basically no free electrolyte within the battery cell, thereby significantly improving the reliability and cycle performance of the battery cell.
[0027] In some embodiments, the lyophilic polymer comprises a fluorinated polymer; the crystallinity of the fluorinated polymer measured by differential scanning calorimetry is Xc1, 0<Xc1≤30%; the melting temperature of the fluorinated polymer is T m1 , its unit is ℃, 0<T m1 ≤140.
[0028] In some embodiments, the glass transition temperature of the fluoropolymer is T g1 , its unit is ℃, -150≤T g1 ≤60.
[0029] In some embodiments, the fluorinated polymer includes at least one of the structural units represented by formula (AI) to the structural units represented by formula (AIII),
[0030] In formula (AI) and formula (AII), R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 、R 12 、R 13 and R 14 At least one of the substituted groups may include a fluorine atom; when substituted, the substituent may include one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom;
[0031] In formula (AIII), R 15 Including single bonds, substituted or unsubstituted C1-C3 alkyl groups; when substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom; p is a positive integer selected from 1 to 3; n is a positive integer selected from 1000 to 30000.
[0032] In some embodiments, the lyophilic polymer further comprises an ether polymer, wherein the ether polymer is made into a sheet structure; the sheet structure is (T m2 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K1, 1<K1<∞, T m2 ℃ represents the melting temperature of the ether polymer; optionally, 1<K1≤100; further optionally, 1<K1≤10.
[0033] In some embodiments, the ether polymer includes a structural unit represented by formula (BI) and / or a structural unit represented by formula (BII),
[0034] In formula (BI), R 21 and R 22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; R 23 Including substituted or unsubstituted C1-C5 alkylene;
[0035] In formula (BII), R 24to R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 alkoxy group or an ether group, and R 24 to R 27 At least one of them contains a substituted or unsubstituted C1-C3 alkoxy group or an ether group.
[0036] In some embodiments, the substituent may include one or more of a nitrile group (—CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom.
[0037] In some embodiments, the lyophilic polymer comprises an ester polymer, wherein the ester polymer is made into a sheet structure; the sheet structure is (T m3 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K2, 1<K2<∞, T m3 ℃ represents the melting temperature of the ester polymer; optionally, 1<K2≤100; further optionally, 1<K2≤10.
[0038] In some embodiments, the ester polymer includes a structural unit represented by formula (CI) and / or a structural unit represented by formula (CII),
[0039] In formula (CI), R 31 、R 32 and R 33 Each independently includes a hydrogen atom, or a substituted or unsubstituted C1-C8 alkyl group; R 34 Including substituted or unsubstituted C1-C8 alkyl, or substituted or unsubstituted C1-C8 hydroxyalkyl;
[0040] In formula (CII), R 35 including substituted or unsubstituted C2-C6 methylene; optionally, R 35 Each independently includes a substituted or unsubstituted C2-C4 methylene group.
[0041] In some embodiments, the substituent may include one or more of a nitrile group (—CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom.
[0042] In some embodiments, the lyophilic polymer comprises an aldehyde-ketone polymer, wherein the aldehyde-ketone polymer is made into a sheet-like structure; the sheet-like structure is (T m4 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K3, 0.8≤K3<∞, Tm4 ℃ represents the melting temperature of the aldehyde-ketone polymer; optionally, 0.8≤K3≤100; further optionally, 0.8≤K3≤10.
[0043] In some embodiments, the aldehyde-ketone polymer comprises a structural unit represented by formula (DI) and / or a structural unit represented by formula (DII),
[0044] In formula (DI), R 41 Including single bonds, substituted or unsubstituted C1-C6 methylene; R 42 including hydrogen atoms, substituted or unsubstituted C1-C6 alkyl groups;
[0045] In formula (DII), R 43 to R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from an integer from 0 to 5, and at least one of r and s is selected from a positive integer.
[0046] In some embodiments, the substituent may include one or more of a nitrile group (—CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom.
[0047] In some embodiments, the molecular weight of the lyophilic polymer is 1.2×10 5 g / mol to 1×10 6 g / mol.
[0048] The second aspect of the present application further provides a battery, comprising a battery cell as described in any embodiment of the first aspect of the present application.
[0049] The third aspect of the present application further provides an electrical device, comprising a battery as described in the embodiment of the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following is a brief introduction to the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0051] FIG1 is a schematic diagram of a battery cell according to an embodiment of the present application.
[0052] FIG. 2 is an exploded schematic diagram of an embodiment of the battery cell of FIG. 1 .
[0053] FIG3 is a schematic diagram of an embodiment of a battery module of the present application.
[0054] FIG4 is a schematic diagram of an embodiment of a battery pack of the present application.
[0055] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .
[0056] FIG6 is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.
[0057] The drawings are not necessarily drawn to scale.
[0058] The accompanying drawings are described as follows: 1. battery pack; 2. upper case; 3. lower case; 4. battery module; 5. battery cell; 51. housing; 52. electrode assembly; 53. cover plate; 6. electrical device. DETAILED DESCRIPTION
[0059] The following detailed description specifically discloses the embodiments of the battery cells, batteries, and electrical devices of the present application. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0060] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0061] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0062] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.
[0063] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may indicate that other components not listed may also be included or that only the listed components are included.
[0064] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0065] In this application, the terms "plurality" and "multiple" refer to two or more.
[0066] Unless otherwise specified, the terms used in this application have the common meanings that are commonly understood by those skilled in the art.
[0067] Unless otherwise stated, the numerical values of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application.
[0068] The term "alkyl" encompasses both straight and branched chain alkyl groups. For example, the alkyl group may be a C1-C5 alkyl group, a C1-C4 alkyl group, a C1-C3 alkyl group, or a C1-C2 alkyl group. In some embodiments, the alkyl group includes a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, and the like. Additionally, the alkyl group may be optionally substituted. When substituted, the substituent includes a fluorine atom.
[0069] The term "alkoxy" refers to a group in which an alkyl group is connected to an oxygen atom by a single bond. For example, the alkoxy group can be a C1 to C5 alkoxy group, a C1 to C3 alkoxy group, or a C1 to C2 alkoxy group. In some embodiments, the alkoxy group can include a methoxy group, an ethoxy group, or a propoxy group. In addition, the alkoxy group can be optionally substituted.
[0070] The term "halogen atom" refers to a fluorine atom, a chlorine atom, a bromine atom or the like.
[0071] The term "hydrogen" refers to 1H (protium, H), 2H (deuterium, D), or 3H (tritium, T). In various embodiments, "hydrogen" may be 1H (protium, H).
[0072] The battery cell includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet. Its main function is to prevent the positive electrode sheet and the negative electrode sheet from short-circuiting, while allowing active ions to pass freely to form a loop.
[0073] The electrolyte is infiltrated into the electrode assembly, allowing active ions to smoothly migrate from the positive electrode of the electrode assembly through the separator to the negative electrode. However, during the use of the battery cell, due to the embedding or extraction of active ions, the volume of the electrode assembly may change (for example, expansion), causing the electrolyte infiltrated into the electrode assembly to be continuously squeezed out. The squeezed-out electrolyte may not be fully absorbed back into the electrode assembly, causing the electrode assembly to lack liquid and localized metal precipitation, increasing the risk of dendrite formation. As the dendrite grows, it may cause the dendrite to pierce the separator, causing a short circuit between the positive and negative electrode sheets, and deteriorating the reliability and cycle performance of the battery cell.
[0074] In response to the above issues, this application proposes a battery cell that incorporates a lyophilic polymer into the electrode assembly. After the lyophilic polymer comes into contact with and mixes with the free electrolyte, the electrolyte is encapsulated between the polymer's molecular chains, forming a condensed electrolyte. This improves the reliability of the battery cell while maintaining its electrical performance. The technical solution of this application is described in detail below.
[0075] battery cells
[0076] In a first aspect, the present application proposes a battery cell, which includes an electrode assembly and an electrolyte, wherein the electrode assembly includes a first electrode piece, a second electrode piece and an isolation membrane, the first electrode piece and the second electrode piece have opposite polarities, and the isolation membrane is arranged between the first electrode piece and the second electrode piece; at least one of the first electrode piece, the second electrode piece and the isolation membrane includes a lyophilic polymer.
[0077] The battery cell satisfies the following formula:
[0078] y represents the mass of the free electrolyte in the battery cell, in g;
[0079] M represents the mass of the battery cell before drying, in g;
[0080] M' represents the mass of the battery cell after drying, and its unit is g.
[0081] In the embodiments of the present application, M-M' can be understood as the total amount of electrolyte in the battery cell. After the electrolyte is injected into the battery cell, the electrolyte mainly exists in the following forms: one is adsorbed in the electrode and / or separator, the second is to form a condensed electrolyte with the lyophilic polymer, and the third is in liquid form and free in the battery cell; y represents the mass of the electrolyte in the third state, that is, the mass of the free electrolyte. The mass of the free electrolyte can be measured by the following method: take a fresh battery cell and fill it to 0% SOC state of charge, weigh the battery cell, and the weighed mass is M; open a hole with a diameter of φ5-8mm in a local position of the battery cell, place the battery cell above a container with the hole facing downward and directly above the container, so that the free electrolyte inside the battery cell can drip into the container below, and let the battery cell stand for 3h to 5h so that the free electrolyte inside can drip into the container, and then weigh the weight of the electrolyte in the container to obtain y. The battery cells are then dried at 60°C to 95°C for 24 to 48 hours, immersed in a dimethyl carbonate (DMC) solvent for 12 hours, and then dried at 60°C to 95°C for 24 to 48 hours. The dried battery cells are weighed, and the weighed mass is recorded as M'. For example, the battery cells are dried at 60°C for 5 hours, and the dried battery cells are weighed. In the embodiment of the present application, the fresh battery cells can be battery cells that have just left the factory (not subjected to charge and discharge cycles after formation), or battery cells that are assembled on electrical devices and have been cycled less than 10 times.
[0082] It represents the ratio of the amount of free electrolyte to the amount of electrolyte in the battery cell, which can characterize the adsorption capacity of the electrode assembly to the electrolyte.
[0083] When the above formula range is satisfied in the embodiments of the present application, the lyophilic polymer and the electrolyte have good affinity, and the electrolyte can quickly diffuse between the molecular chains of the lyophilic polymer and be wrapped by the molecular chains. After swelling and adsorption, an elastic porous slow-release electrolyte is obtained. The slow-release electrolyte can absorb the free electrolyte in the battery cell, reducing the presence of free electrolyte. Since the free electrolyte is locked, the risk of the free electrolyte being squeezed out is reduced, thereby reducing the risk of short-circuiting the positive and negative electrode sheets due to dendrite formation, and improving the reliability and cycle performance of the battery cell. In addition, the absorbed free electrolyte forms a new condensed electrolyte with the elastic porous slow-release electrolyte, which can ensure that the electrolyte has a high electrical conductivity, thereby improving the electrical performance of the battery cell.
[0084] Therefore, the embodiments of the present application satisfy When, further, satisfy When, especially when satisfied At the same time, it is possible to further improve the reliability and cycle performance of the battery cell.
[0085] For example, Can be
[0086] 0%、0.001%、0.002%、0.003%、0.004%、0.005%、0.006%、0.007%、0.008%、0.009%、0.01%、0.012%、0.014%、0.016%、0.018%、0.02%、0.022%、0.024%、0.026%、0.028%、0.03%、0.032%、0.034%、0.036%、0.038%、0.04%、0.042%、0.044%、0.046%、0.048%、0.05%、0.052%、0.054%、0.056%、0.058%、0.06%、0.062%、0.064%、0.066%、0.068%、0.07%、0.072%、0.074%、0.076%、0.078%、0.08%、0.082%、0.084%、0.086%、0.088%、0.09%、0.092%、0.094%、0.096%、0.098%、0.10%、0.15%、0.20%、0.25%、0.30%、0.35%、0.40%、0.45%、0.50%、0.55%、0.60%、0.65%、0.70%、0.75%、0.80%、0.85%、0.90%、0.95%、1.00%、 1.10%、1.20%、1.30%、1.40%、1.50%、1.60%、1.70%、1.80%、1.90%、2.00%、2.10%、2.20%、2.30%、2.40%、2.50%、2.60%、2.70%、2.80%、2.90%、3.00%、3.10%、3.20%、3.30%、3.40%、3.50%、3.60%、3.70%、3.80%、3.90%、4.00%、4.10%、4.20%、4.30%、4.40%、4.50%、4.60%、4.70%、4.80%、4.90%、5.00%、5.10%、5.20%、5.30%、5.40%、5.50%、5.60%、5.70%、5.80%、5.90%、6.00%、6.10%、6.20%、6.30%、6.40%、6.50%、6.60%、6.70%、6.80%、6.90%、7.00%、7.10%、7.20%、7.30%、7.40%、7.50%、7.60%、7.70%、7.80%、7.90%、8.00%、8.10%、8.20%、8.30%、8.40%、8.50%、8.60%、8.70%、8.80%、8.90%、9.00%、9.10%、9.20%、9.30%、9.40%、9.50%、9.60%, 9.70%, 9.80%, 9.90%, 10%, 10.10%, 10.20%, 10.30%, 10.40%, 10.50%, 10.60%, 10.70%, 10.80%, 10.90%, 11.00%, 11.10%, 11.20%, 11.30%, 11.40%, 11.50%, 11.60%, 11.70%, 11.80%, 11.90%, 12.00%, 12.10%, 12.20%, 12.30%, 12.40%, 1 2.50%, 12.60%, 12.70%, 12.80%, 12.90%, 13.00%, 13.10%, 13.20%, 13.30%, 13.40%, 13.50%, 13.60%, 13.70%, 13.80%, 13.90%, 14.00%, 14.10%, 14.20%, 14.30%, 14.40%, 14.50%, 14.60%, 14.70%, 14.80%, 14.90%, 15.00%, or a range consisting of any two of the above values.
[0087] The embodiments of the present application can further improve both the reliability and cycle performance of the battery cells when the following conditions are met.
[0088] In some embodiments, the battery cell further satisfies the following formula:
[0089] Optionally,
[0090] m1 represents the mass of the electrode assembly before drying, and its unit is g; the mass before drying represents the mass of the electrode assembly obtained by disassembling the battery cell, removing the electrode assembly, and standing the electrode assembly for 3 to 5 hours to allow the free electrolyte in the electrode assembly to flow out.
[0091] m2 represents the mass of the electrode assembly after drying, and its unit is g; the mass after drying represents the mass of the electrode assembly obtained after drying and removing the electrolyte adsorbed by the electrode assembly, for example, the electrode assembly is placed in an oven at 60°C to 95°C for 24 to 48 hours, the electrode assembly is immersed in dimethyl carbonate DMC solvent and fully immersed for 12 hours, and then the electrode assembly is placed in an oven at 60°C to 95°C for 24 to 48 hours, and the dried electrode assembly is weighed. The obtained electrode assembly is the dried electrode assembly.
[0092] m2-m1 represents the mass of electrolyte adsorbed in the electrode assembly; It represents the ratio of the mass of free electrolyte to the mass of electrolyte adsorbed in the electrode assembly, which can characterize the ability of the electrode assembly to adsorb electrolyte.
[0093] The implementation method of this application satisfies the above formula range. When the battery is powered, the reliability of the battery cell can be further improved. Can be
[0094] 0%、0.001%、0.002%、0.003%、0.004%、0.005%、0.006%、0.007%、0.008%、 0.009%、0.01%、0.012%、0.014%、0.016%、0.018%、0.02%、0.022%、0.024%、0.026%、0.028%、0.03%、0.032%、0.034%、0.036%、0.038%、0.04%、0.042%、0.044%、0.046%、0.048%、0.05%、0.052%、0.054%、0.056%、0.058%、0.06%、0.062%、0.064%、0.066%、0.068%、0.07%、0.072%、0.074%、0.076%、0.078%、0.08%、0.082%、0.084%、0.086%、0.088%、0.09%、0.092%、0.094%、0.096%、0.098%、0.10%、0.15%、0.20%、0.25%、0.30%、0.35%、0.40%、0.45%、0.50%、0.55%、0.60%、0.65%、0.70%、0.75%、0.80%、0.85%、0.90%、0.95%、1.00%、1.10%、1.20%、1.30%、1.40%、1.50%、1.60%、1.70%、1.80%、1.90%、2.00%、2.10%、2.20%、2.30%、2.40%、2.50%、2.60%、2.70%、2.80%、2.90%、3.00%、3.10%、3.20%、3.30%、3.40%、3.50%、3.60%、3.70%、3.80%、3.90%、4.00%、4.10%、4.20%、4.30%、4.40%、4.50%、4.60%、4.70%、4.80%、4.90%、5.00%、5.10%、5.20%、5.30%、5.40%、5.50%、5.60%、5.70%、5.80%、5.90%、6.00%、6.10%、6.20%、6.30%、6.40%、6.50%、6.60%、6.70%、6.80%、6.90%、7.00%、7.10%、7.20%、7.30%、7.40%、7.50%、7.60%、7.70%、7.80%、7.90%、8.00%、8.10%、8.20%、8.30%、8.40%、8.50%、8.60%、8.70%、8.80%、8.90%、9.00%、9.10%、9.20%、9.30%、9.40%、9.50%、9.60%, 9.70%, 9.80%, 9.90%, 10%, or a range consisting of any two of the above values.
[0095] In some embodiments, the battery cell further satisfies the following formula: Optionally,
[0096] It represents the ratio of the mass of free electrolyte to the mass of the electrode assembly after drying, that is, the content of free electrolyte corresponding to the unit mass of the dried electrode assembly, which can characterize the content of electrolyte that can be adsorbed by the electrode assembly.
[0097] The implementation method of this application satisfies the above formula range. When the battery is used, the reliability of the battery cell can be further improved. Can be
[0098] 0%, 0.001%, 0.002%, 0.003%, 0.004%, 0.005%, 0.006%, 0.007%, 0.008%, 0.009%, 0.01%, 0.012%, 0.014%, 0.016%, 0.018%, 0.02%, 0.022%, 0.024%, 0.026%, 0.028%, 0. 03%, 0.032%, 0.034%, 0.036%, 0.038%, 0.04%, 0.042%, 0.044%, 0.046%, 0.048%, 0.05%, 0.052%, 0.054%, 0.056%, 0.058%, 0.06%, 0.062%, 0.064%, 0.066%, 0.068%, 0.0 7%, 0.072%, 0.074%, 0.076%, 0.078%, 0.08%, 0.082%, 0.084%, 0.086%, 0.088%, 0.09%, 0.092%, 0.094%, 0.096%, 0.098%, 0.10%, 0.15%, 0.20%, 0.25%, 0.30%, 0.35%, 0 .40%, 0.45%, 0.50%, 0.55%, 0.60%, 0.65%, 0.70%, 0.75%, 0.80%, 0.85%, 0.90%, 0.95%, 1.00%, 1.10%, 1.20%, 1.30%, 1.40%, 1.50%, 1.60%, 1.70%, 1.80%, 1.90%, 2.00%, 2.10%, 2.20%, 2.30%, 2.40%, 2.50%, 2.60%, 2.70%, 2.80%, 2.90%, 3.00%, 3.10%, 3.20%, 3.30%, 3.40%, 3.50%, 3.60%, 3.70%, 3.80%, 3.90%, 4.00%, 4.10%, 4.20%, 4.30%, 4.40%, 4.50%, 4.60%, 4.70%, 4.80%, 4.90%, 5.00% or a range consisting of any two of the above values.
[0099] In some embodiments, the amount of free electrolyte per unit capacity of the battery cell is b, with the unit being mg / Ah, and 0≤b≤1400. When the amount of free electrolyte per unit capacity of the battery cell b satisfies the above range, the reliability and cycle performance of the battery cell can be further improved.
[0100] Optionally, 0.1≤b≤1000; further optionally, 0.3≤b≤800. For example, the amount of free electrolyte per unit capacity of the battery cell may be 0 mg / Ah, 0.001 mg / Ah, 0.002 mg / Ah, 0.003 mg / Ah, 0.004 mg / Ah, 0.005 mg / Ah, 0.006 mg / Ah, 0.007 mg / Ah, 0.008 mg / Ah, 0.009 mg / Ah, 0.01 mg / Ah, 0.02 mg / Ah, 0 .03mg / Ah, 0.04mg / Ah, 0.05mg / Ah, 0.06mg / Ah, 0.07mg / Ah, 0.08mg / Ah, 0.09mg / Ah, 0.1mg / A h, 0.2mg / Ah, 0.3mg / Ah, 0.5mg / Ah, 1.0mg / Ah, 5.0mg / Ah, 10.0mg / Ah, 20.0mg / Ah, 50.0mg / Ah , 80.0mg / Ah, 100mg / Ah, 120mg / Ah, 150mg / Ah, 180mg / Ah, 200mg / Ah, 220mg / Ah, 250mg / Ah, 30 0mg / Ah, 350mg / Ah, 400mg / Ah, 450mg / Ah, 500mg / Ah, 550mg / Ah, 600mg / Ah, 650mg / Ah, 700mg / Ah, 750 mg / Ah, 800 mg / Ah, 850 mg / Ah, 900 mg / Ah, 950 mg / Ah, 1000 mg / Ah, 1050 mg / Ah, 1100 mg / Ah, 1150 mg / Ah, 1200 mg / Ah, 1250 mg / h, 1300 mg / Ah, 1350 mg / Ah, 1400 mg / Ah, or a range consisting of any two of the foregoing values.
[0101] In the embodiment of the present application, b is equal to y / x, where x represents the nominal capacity of the battery cell, in Ah, and y is the mass of the free electrolyte mentioned above.
[0102] In the embodiment of the present application, x can be detected using methods and equipment known in the art, for example, the product of all currents that can be output when the battery cell is fully charged and discharged at a constant current and constant voltage of 0.33C to the termination voltage and the discharge time.
[0103] In some embodiments, after the battery cell is subjected to a linear frequency sweep vibration test, it is charged to 100% state of charge (SOC). A hole is opened on the battery cell, and the hole is located at the lowest point in the vertical direction. The mass of the electrolyte flowing out of the battery cell is recorded as M1, where 0≤M1≤6g. Optionally, M1 is 0g.
[0104] in,
[0105] The vibration direction of the linear sweep vibration test is: single vibration up and down;
[0106] The vibration frequency of the linear sweep vibration test is: 10Hz~55Hz;
[0107] The maximum acceleration of the linear sweep vibration test is: 30m / s2;
[0108] The number of sweep cycles of the linear sweep vibration test is: 10 times;
[0109] The vibration time of the linear sweep frequency vibration test is 3 hours.
[0110] In the related art, during use, battery cells may vibrate under the action of external forces, and the electrolyte in the electrode assembly may separate from the electrode assembly under the action of vibration, forming free electrolyte. The free electrolyte in the battery cell may leak, causing corrosion to the battery cell and leading to risks such as battery cell failure. However, the embodiments of the present application can effectively gather and throw out the electrolyte inside the battery cell by subjecting the battery cell to static and vibration treatment, thereby more accurately judging whether there is flowing electrolyte between the battery cell shell and the electrode assembly, and determining the content of free electrolyte. When the battery cell of the embodiments of the present application meets the above conditions, the content of free electrolyte in the battery cell is extremely small, or even the battery cell basically contains no free electrolyte, which can significantly improve the reliability and cycle performance of the battery cell.
[0111] Illustratively, M1 can be 0, 0.05g, 0.10g, 0.15g, 0.20g, 0.25g, 0.3g, 0.35g, 0.4g, 0.45g, 0.5g, 0.55g, 0.60g, 0.65g, 0.70g, 0.75g, 0.80g, 0.85g, 0.90g, 0.95g, 1.00g, 1.10g, 1.20g, 1.30g, 1.40g, 1.50g, 1.60g, 1.70g, 1.80g, 1.90g, 2.00g, 2.10g, 2.20g, 2.30g, 2.40g, 2.50g, 2.60g, 2.70g, 2.80g, 2.90g, 3.00g, 3.10g, 3.20g, 3.30g, 3.40g, 3.50g, 3.60g, 3.70g, 3.80g, 3.90g, 4.00g, 4.10g, 4.20g, 4.30g, 4.40g, 4.50g, 4.60g, 4.70g, 4.80g, 4.90g, 5.00g, 6.00g, or a range consisting of any two of the above values. M1 is 0g, indicating that the amount of free electrolyte is 0, that is, there is substantially no free electrolyte inside the battery cell after the linear frequency sweep vibration test.
[0112] In some embodiments, after the battery cell undergoes the above-mentioned linear frequency sweep vibration test, the shell is removed, the electrode assembly is taken out and subjected to an extrusion test, and the volume of the electrolyte flowing out of the electrode assembly is recorded as M2 (the extrusion equipment is suspended, and a weighing balance and an electrolyte collection container are set at the bottom), 0≤M2≤0.6g, optionally, M2 is 0g; wherein,
[0113] The extrusion direction of the extrusion test is: perpendicular to the thickness direction of the electrode assembly;
[0114] The extrusion degree of the extrusion test is: the extrusion force is 0.35 MPa.
[0115] In the related art, during use, battery cells may be subjected to external squeezing, and the electrolyte in the electrode assembly may be separated from the electrode assembly under the squeezing action, forming free electrolyte. The free electrolyte in the battery cell may leak, causing corrosion to the battery cell, leading to risks such as battery cell failure. However, the embodiment of the present application can effectively squeeze out the electrolyte inside the battery cell by performing an squeezing test on the battery cell, thereby more accurately judging whether there is flowing electrolyte between the battery cell shell and the electrode assembly, and determining the content of free electrolyte. When the battery cell of the embodiment of the present application meets the above conditions, the content of free electrolyte in the battery cell is extremely small, or even basically contains no free electrolyte in the battery cell, which can significantly improve the reliability and cycle performance of the battery cell.
[0116] Illustratively, M2 can be 0, 0.05 mg, 0.10 mg, 0.15 mg, 0.20 mg, 0.25 mg, 0.3 mg, 0.35 mg, 0.4 mg, 0.45 mg, 0.5 mg, 0.55 mg, 0.60 mg, 0.65 mg, 0.70 mg, 0.75 mg, 0.80 mg, 0.85 mg, 0.90 mg, 0.95 mg, 1.00 mg, 1.10 mg, 1.20 mg, 1.30 mg, 1.40 mg, 1.50 mg, 1. 60mg, 1.70mg, 1.80mg, 1.90mg, 2.00mg, 2.10mg, 2.20mg, 2.30mg, 2.40mg, 2.50mg, 2.60mg, 2.70mg, 2.80mg, 2.90 mg, 3.00mg, 3.10mg, 3.20mg, 3.30mg, 3.40mg, 3.50mg, 3.60mg, 3.70mg, 3.80mg, 3.90mg, 4.00mg, 4.10mg, 4.20mg , 4.30mg, 4.40mg, 4.50mg, 4.60mg, 4.70mg, 4.80mg, 4.90mg, 5.00mg, 10.00mg, 20.00mg, 30.00mg, 40.00mg, 50.0 0mg, 60.00mg, 70.00mg, 80.00mg, 90.00mg, 100.00mg, 110.00mg, 120.00mg, 130.00mg, 140.00mg, 150.00mg, 160 .00mg, 170.00mg, 180.00mg, 190.00mg, 200.00mg, 210.00mg, 220.00mg, 230.00mg, 240.00mg, 250.00mg, 260.00 mg, 270.00mg, 280.00mg, 290.00mg, 300.00mg, 310.00mg, 320.00mg, 330.00mg, 340.00mg, 350.00mg, 360.00mg, 370.00mg, 380.00mg, 390.00mg, 400.00mg, 410.00mg, 420.00mg, 430.00mg, 440.00mg, 450.00mg, 460.00mg, 470.00mg, 480.00mg, 490.00mg, 500.00mg, 510.00mg, 520.00mg, 530.00mg, 540.00mg, 550.00mg, 560.00mg, 570.00mg, 580.00mg, 590.00mg, 600.00mg or a range consisting of any two of the above values.M2 is 0g, indicating that the amount of free electrolyte is 0, that is, after the battery cell is subjected to the extrusion test, there is substantially no free electrolyte inside the cell.
[0117] In some embodiments, a voltage of 200 V is provided to the battery cell to form a loop for 4 hours, and the absolute value of the temperature change of the battery cell is ≤ 4°C.
[0118] For example, when the negative terminal and outer casing of a battery cell are connected to a 200V voltage to form a current loop, the battery cell's temperature fluctuates within 4°C over a 4-hour period, without any failures such as fire or explosion. In particular, when the free electrolyte y = 0, the temperature fluctuation range is minimal, significantly improving the reliability of the battery cell.
[0119] In some embodiments, the electrode sheet includes a lyophilic polymer. Specifically, the first electrode sheet includes a current collector and an active material layer disposed on at least one surface of the current collector, wherein the active material layer includes a lyophilic polymer and active material particles. The lyophilic polymer may be disposed only in the first electrode sheet or only in the second electrode sheet, or the lyophilic polymer may be disposed in both the first and second electrode sheets. The first electrode sheet may be a positive electrode sheet, and accordingly, the second electrode sheet may be a negative electrode sheet; alternatively, the first electrode sheet may be a negative electrode sheet, and accordingly, the second electrode sheet may be a positive electrode sheet.
[0120] As some examples, the lyophilic polymer is distributed on the surface of the active material particles; it can be understood that the active material particles and the binder are solidified into a film layer on the surface of the current collector, and the lyophilic polymer is arranged on the surface of the film layer away from the current collector. Such a setting can enable the electrolyte to quickly diffuse between the molecular chains of the lyophilic polymer and be wrapped by the molecular chains, forming a gel-like substance on the surface of the active material particles and adhering to the surface of the active material particles to protect the active material particles, thereby closely connecting the active material particles and the electrolyte, improving the solid-liquid interface performance, reducing the side reactions between the active material particles and the electrolyte, and improving the reliability and electrical performance (such as cycle performance and storage performance) of the battery cell.
[0121] Specifically, the electrode preparation process includes:
[0122] adding active material particles into a solvent to prepare an active slurry;
[0123] Applying the active slurry to the surface of the current collector and solidifying it into a film layer after drying;
[0124] The lyophilic polymer is placed on the surface of the membrane layer to form an electrode.
[0125] As other examples, there are multiple active material particles, with pores between two adjacent active material particles, and the lyophilic polymer is distributed in the pores between the active material particles; this setting can improve the liquid storage capacity of the active material layer, that is, the ability to lock the electrolyte, thereby improving the reliability and electrical performance of the battery cell.
[0126] Specifically, the preparation process of an embodiment of a pole piece includes:
[0127] dispersing the lyophilic polymer in a solvent to form a mixed system;
[0128] Adding active material particles into the mixed system to prepare a slurry;
[0129] The slurry is applied to the surface of the current collector and dried and solidified to form a pole piece.
[0130] Specifically, the preparation process of another embodiment of the pole piece includes:
[0131] Dispersing the lyophilic polymer and active material particles in a solvent to prepare a slurry;
[0132] The slurry is applied to the surface of the current collector and dried and solidified to form a pole piece.
[0133] As some further examples, the lyophilic polymer is distributed on the surface of the active material particles, and the lyophilic polymer is distributed in the pores between the active material particles.
[0134] Specifically, the preparation process of an embodiment of a pole piece includes:
[0135] Dispersing the lyophilic polymer and active material particles in a solvent to prepare a slurry;
[0136] Applying the slurry on the surface of the current collector and solidifying it into a film layer after drying;
[0137] The lyophilic polymer is placed on the surface of the membrane layer to form an electrode.
[0138] In other embodiments, the isolation membrane includes a lyophilic polymer. Specifically, the isolation membrane may include a substrate; optionally, the isolation membrane may further include a coating disposed on at least one surface of the substrate.
[0139] As some examples, the substrate is generally a porous structure having pores, and the lyophilic polymer may be distributed in the pores of the substrate.
[0140] As other examples, the lyophilic polymer may be distributed within the coating.
[0141] As yet some further examples, the lyophilic polymer may be disposed on a surface of the coating layer facing away from the substrate.
[0142] The specific distribution position of the lyophilic polymer can be any one of the above three forms, any two of them, or a combination of the above three positions.
[0143] In some further embodiments, the lyophilic polymer may be disposed in the electrode and the isolation membrane. The specific location of the arrangement is as described above and will not be repeated here.
[0144] In some embodiments, the lyophilic polymer may include one or more of a fluorine-based polymer, an ether-based polymer, an ester-based polymer, and a ketone-aldehyde-based polymer.
[0145] [Fluoropolymers]
[0146] In some embodiments, the lyophilic polymer comprises a fluorinated polymer, wherein the crystallinity of the fluorinated polymer measured by differential scanning calorimetry is X C1 %,0<X C1 ≤30; the melting temperature of the fluoropolymer is T m1 , its unit is ℃, 0<T m1 ≤140.
[0147] Crystallization refers to the process in which atoms, ions or molecules in a material are arranged in a certain spatial order to form an orderly structure. The conformation of the polymer in the crystallization is determined by both intramolecular and intermolecular factors. The intermolecular force will affect the packing density between molecular chains. C1 % is used to characterize the degree of crystallinity in the material, which can be measured by differential scanning calorimetry (DSC). Specifically, the test steps are as follows: take 0.5g to 0.8g of sample, place the sample in a carrier crucible, and perform temperature rise and fall treatment on the sample under a nitrogen atmosphere, with a heating rate of 10℃ / min from the intrinsic T g1 The initial temperature is 20℃ lower and then heated to the intrinsic T m1 The cut-off temperature of the process is 20℃ higher. The actual glass transition temperature T of the material is determined according to the endothermic and exothermic peak or transition point of the material in the process. g1 and melting temperature T m1 wait.
[0148] As a result, fluoropolymers have relatively low crystallinity and melting temperature, which makes the molecular chains tend to be loose, the interaction force between the molecular chains is small, adjacent molecular chains are easily opened, and the chain segment movement is achieved through intermolecular rotation, forming a molecular chain structure with high flexibility; and the fluoropolymers and the electrolyte in the battery cell can form a gel-like substance, improving the reliability and cycle performance of the battery cell.
[0149] For example, the crystallinity X of the fluorinated polymer measured by differential scanning calorimetry is C1% can be 5%, 10%, 15%, 20%, 25%, 30% or a range consisting of any two of the above values.
[0150] For example, the melting temperature of the fluorinated polymer may be 10° C., 20° C., 50° C., 70° C., 90° C., 100° C., 120° C., 140° C., or a range consisting of any two of the foregoing values.
[0151] In some embodiments, the glass transition temperature of the fluorinated polymer is T g1 , its unit is ℃, -150≤T g1 ≤60.
[0152] The glass transition temperature is the temperature at which the chain segments of a polymer transition from freezing to movement. The glass transition temperature has a certain influence on the flexibility of the polymer molecular chain. The lower the glass transition temperature, the better the flexibility of the polymer molecular chain at room temperature. The higher the glass transition temperature, the worse the flexibility of the molecular chain at room temperature. The glass transition temperature can be measured by differential scanning calorimetry (DSC). The lower the glass transition temperature of a polymer, the better the segment flexibility of the molecular chain, and the easier it is for adjacent molecular chains to be opened. For example, the glass transition temperature of a fluorinated polymer can be -150°C, -120°C, -100°C, -80°C, -60°C, -30°C, 0°C, 30°C, 60°C, or a range consisting of any two of the above values.
[0153] In some embodiments, the fluorinated polymer comprises at least one of the structural units represented by formula (AI) to the structural units represented by formula (AIII),
[0154] In formula (AI) and formula (AII), R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 、R 12 、R 13 and R 14 At least one of the substituted groups may contain a fluorine atom; when substituted, the substituent may include one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom.
[0155] In formula (AIII), R 15The present invention includes single bonds, substituted or unsubstituted C1-C3 alkyl groups. When substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom. p is a positive integer selected from 1 to 3. n is a positive integer selected from 1,000 to 30,000.
[0156] In some embodiments, R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C2 alkyl group or a substituted or unsubstituted C1-C2 alkoxy group; further optionally, R 11 、R 12 、R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, a fluoromethyl group, a methoxy group or a perfluoromethoxy group.
[0157] In some embodiments, the fluorinated polymer includes at least one of the structural units represented by formula (AI-1) to the structural units represented by formula (AI-11),
[0158] In some embodiments, the fluorinated polymer includes at least one of the structural units represented by formula (AII-1) to the structural units represented by formula (AII-5),
[0159] In some embodiments, the fluorinated polymer includes at least one of the structural units represented by formula (AIII-1) to the structural units represented by formula (AIII-3),
[0160] Illustratively, the fluorinated polymer includes one or more of polyperfluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroethylene propylene copolymer (FEP), perfluoroalkoxy polymer (PFA), perfluoropolyether (PFPE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE) and perfluoro (1-butenyl vinyl ether) polymer (CYTOP for short).
[0161] Optionally, the fluorinated polymer includes one or more of polyperfluoroethylene (PTFE), polyvinylidene fluoride (PVDF), perfluoroethylene propylene copolymer (FEP), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), and polyvinylidene fluoride-trifluoroethylene copolymer (PVDF-TrFE).
[0162] The fluoropolymer may be derived from one or more of the following monomers: fluorocycloethane, vinyl fluoride, 1,2-difluoroethylene, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropylene, trifluoropropylene, tetrafluoropropylene, and pentafluoropropylene. Alternatively, the fluoropolymer may be derived from at least two of the following monomers: fluorocycloethane, vinyl fluoride, 1,2-difluoroethylene, vinylidene fluoride, trifluoroethylene, chlorotrifluoroethylene, tetrafluoroethylene, hexafluoropropylene, 3,3,3-trifluoropropylene, trifluoropropylene, tetrafluoropropylene, and pentafluoropropylene.
[0163] The monomers used in the above-mentioned fluorinated polymers are all short-chain monomers, which are conducive to the polymerization to form a straight-chain linear structure or a short-chain branched structure. This type of structure has a low degree of entanglement, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte, thereby further improving the interfacial performance of the active material.
[0164] In some embodiments, n is a positive integer selected from 5000 to 20000; and / or the molecular weight of the lyophilic polymer is 2×10 5 g / mol to 1.5×10 6 When the polymer molecular weight is within the above range, it can ensure a certain solubility of the polymer in the electrolyte while being difficult to be completely dissolved and dispersed by the electrolyte, which is beneficial for regulating the distribution and dispersion of the polymer on the surface of the active material. It can also further improve the flexibility between the polymer molecular chains. The interaction between the molecular chains is relatively weak, which facilitates the solvent molecules in the electrolyte to open the molecular chains, enter between the molecular chains, and be wrapped by the molecular chains. This facilitates the entry of active ions into the active material through the solvent, achieving smooth and rapid migration of active ions.
[0165] For example, the molecular weight of the polymer may be 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.5×10 6 g / mol or a range consisting of any two of the above values.
[0166] [Ether polymers]
[0167] In some embodiments, the lyophilic polymer includes an ether polymer, and the ether polymer is made into a sheet structure; the sheet structure is (T m2 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K1, 1<K1<∞, Tm2 °C represents the melting temperature of the ether polymer.
[0168] Specifically, the sheet structure is prepared as follows: the ether polymer is vacuum dried at 80°C for 12 hours. The dried ether polymer is hot-pressed into a sheet by a flat vulcanizer, and the hot-pressing temperature is set to (T m2 The sample is then removed from the press after 2 minutes of calendering and placed on another vulcanizing press of the same model for cold pressing at a pressure of 10 MPa. A polymer disc (sheet structure) of fixed size is obtained using a circular mold with a diameter of 25 mm. For example, the sheet structure can be a disc with a thickness of 1-2 mm and a diameter of 25 mm; alternatively, a sample can be prepared according to the sample standard required by the test equipment.
[0169] According to the conclusions of classical linear viscoelasticity, for polymers, especially linear polymers, the elastic modulus G'-dissipation modulus G" in the terminal region of the elastic modulus G'-dissipation modulus G" curve (the interval approaching the maximum angular velocity) conforms to frequency dependence, and the longest chain of the polymer plays a role in the viscoelastic behavior.
[0170] The specific steps of the dynamic frequency sweep test are as follows: The dynamic frequency sweep test was performed using a TA-AR2000EX rotational rheometer (TAinstruments, USA) with a parallel plate diameter of 25 mm and a thickness of 0.9 mm. To ensure that the test was in the linear point-bounce region, the strain during the dynamic frequency sweep test was 2% and the test temperature was T m2 +20℃, test frequency sweep range: 500rad / s≤w 2 ≤0.05rad / s, so as to obtain data in the lowest possible frequency range.
[0171] The dynamic frequency sweep test can characterize the degree of entanglement of molecular chains under solid-phase melting (melt state). Compared with linear structures or short-chain branched structures, long-branched structures, network structures, and low-crosslinked structures have a high degree of entanglement, which will show deviation from linear terminal behavior. Ether polymers exhibit solid-phase behavior. When the ether polymers of the present application meet the above range, the entanglement state of the molecular chains can be further reduced, which is conducive to the diffusion of solvent molecules in the electrolyte between the molecular chains; moreover, the ether polymers still maintain a certain degree of molecular chain entanglement and can form a gel-like substance with the electrolyte, thereby improving the cycle performance and storage performance of the battery cell.
[0172] In some embodiments, 1<K1≤100; alternatively, 1<K1≤10. For example, K1 can be 0.8, 0.9, 1, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000, or a range consisting of any two of the above values.
[0173] In some embodiments, the glass transition temperature of the ether polymer is T g2 , its unit is ℃, -100≤T g2 ≤50; optionally, -80≤T g2 ≤30. For example, the glass transition temperature of the ether polymer may be -100°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range consisting of any two of the above values.
[0174] In some embodiments, the ether polymer includes a structural unit represented by formula (BI),
[0175] In formula (BI), R 21 and R 22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; R 23 including substituted or unsubstituted C1-C5 methylene; optionally, R 21 and R 22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C2 alkyl group; and / or R 23 It includes single bonds, substituted or unsubstituted C1-C4 methylene groups.
[0176] In some embodiments, when substituted, the substituent may include one or more of a nitrile group (—CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom.
[0177] Illustratively, the ether polymer includes at least one of the structural units represented by formula (BI-1) to the structural units represented by formula (BI-8),
[0178] In some embodiments, the ether polymer comprises a structural unit represented by formula (BII),
[0179] In formula (BII), R 24 to R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 alkoxy group or an ether group, and R 24 to R27 At least one of them contains a substituted or unsubstituted C1-C3 alkoxy group or an ether group.
[0180] Optionally, R 24 to R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C2 alkyl group, a substituted or unsubstituted C1-C2 alkoxy group or an ether group, and R 24 to R 27 At least one of them contains a substituted or unsubstituted C1-C2 alkoxy group or an ether group.
[0181] In some embodiments, the ether polymer includes at least one of the structural units represented by formula (BII-1) to the structural units represented by formula (BII-7),
[0182] The monomers used in the above-mentioned ether polymers are polycyclic rings, such as structures with six or less members, or short-chain monomers, which are conducive to the polymerization to form a high-content -O- structure. This type of structure has a low degree of entanglement, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte and easily form a gel-like substance with the electrolyte, thereby improving the cycle performance and storage performance of the battery monomer.
[0183] The above polymers are merely examples of the structural groups of the main molecular chain. In the embodiments of the present application, the polymers may also be obtained by copolymerizing the above structural groups with other types of structural groups (such as olefin structural units, acrylonitrile structural units, etc.).
[0184] When the above-mentioned groups are substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom. These substituents are high-pressure-resistant substituents, which are more conducive to stabilizing the structure of the polymer. Halogen atoms may include fluorine atoms, chlorine atoms, bromine atoms, and the like.
[0185] In some embodiments, n is a positive integer selected from 1,500 to 25,000.
[0186] Optionally, n is a positive integer selected from 3000 to 18000.
[0187] In some embodiments, the molecular weight of the polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.
[0188] For example, the molecular weight of the polymer may be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×105 g / mol, 1×10 6 g / mol or a range consisting of any two of the above values.
[0189] [Ester polymer]
[0190] In some embodiments, the lyophilic polymer comprises an ester polymer, wherein the ester polymer is made into a sheet structure; the sheet structure is (T m3 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K2, 1<K2<∞, T m3 °C represents the melting temperature of the ester polymer.
[0191] When the ester polymer of the present application meets the above range, the entanglement state of the molecular chains can be further reduced, which is beneficial to the diffusion of solvent molecules in the electrolyte between the molecular chains; and the ether polymer still maintains a certain molecular chain entanglement state, and can form a gel-like substance with the electrolyte, thereby improving the cycle performance and storage performance of the battery cell.
[0192] In some embodiments, 1<K2≤100; optionally, 1<K2≤10.
[0193] Illustratively, K2 may be 1.01, 1.1, 1.2, 1.5, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000, or a range consisting of any two of the above values.
[0194] In some embodiments, the glass transition temperature of the ester polymer is T g3 , its unit is ℃, -100≤T g3 ≤50; optionally, -80≤T g3 ≤30.
[0195] For example, the glass transition temperature of the ester polymer may be -100°C, -90°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range consisting of any two of the above values.
[0196] In some embodiments, the ester polymer comprises a structural unit represented by formula (CI),
[0197] In formula (CI), R 31 、R 32 and R 33 Each independently includes a hydrogen atom, or a substituted or unsubstituted C1-C8 alkyl group; R 34Including substituted or unsubstituted C1-C8 alkyl, or substituted or unsubstituted C1-C8 hydroxyalkyl; optionally, R 34 It includes substituted or unsubstituted C1-C6 alkyl groups, or substituted or unsubstituted C1-C6 hydroxyalkyl groups.
[0198] Optionally, R 31 including a hydrogen atom, or a substituted or unsubstituted methyl group; R 32 and R 33 Each independently includes a hydrogen atom; R 34 It includes substituted or unsubstituted C1-C4 alkyl groups, or substituted or unsubstituted C1-C4 hydroxyalkyl groups.
[0199] Illustratively, the ester polymer includes at least one of the structural units represented by formula (CI-1) to the structural units represented by formula (CI-15),
[0200] In some embodiments, the ester polymer comprises a structural unit represented by formula (CII),
[0201] In formula (CII), R 35 including substituted or unsubstituted C2-C6 methylene; optionally, R 35 Each independently includes a substituted or unsubstituted C2-C4 methylene group.
[0202] Illustratively, the ester polymer includes at least one of the structural units represented by formula (CII-1) to the structural units represented by formula (CII-5),
[0203] The molecular chains of the above-mentioned ester polymers have a low degree of entanglement, which is conducive to improving the flexibility of the molecular chains. The molecular chains can fully stretch in the electrolyte and easily form a gel-like substance with the electrolyte.
[0204] The above-mentioned polymers are only examples of the structural groups of the main molecular chain. In the embodiments of the present application, the polymers can also be obtained by copolymerizing the above-mentioned structural groups with other types of structural groups (such as olefin structural units, acrylonitrile structural units, maleic anhydride and other monomers with functional groups).
[0205] When the above groups are substituted, the substituents may include one or more of a nitrile group, a nitro group, a sulfonyl group, a carboxyl group, an ester group, a chlorine atom, a fluorine atom, and a bromine atom. The above substituents are high-pressure-resistant substituents, which are more conducive to stabilizing the structure of the polymer.
[0206] In some embodiments, n is a positive integer selected from 800 to 20,000.
[0207] Optionally, n is a positive integer selected from 1000 to 15000.
[0208] In some embodiments, the molecular weight of the polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.
[0209] For example, the molecular weight of the polymer may be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.5×10 6 g / mol or a range consisting of any two of the above values.
[0210] [Ketone-aldehyde polymers]
[0211] In some embodiments, the lyophilic polymer comprises an aldehyde-ketone polymer, wherein the aldehyde-ketone polymer is made into a sheet structure; the sheet structure is (T m4 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency sweep test at +20)℃. The slope of the elastic modulus G'-energy loss modulus G" curve is K3, 0.8≤K3<∞, T m4 °C represents the melting temperature of the aldehyde-ketone polymer.
[0212] In some embodiments, 0.8≤K3≤100; optionally, 0.8≤K3≤10.
[0213] Illustratively, K3 may be 0.8, 0.9, 1, 2, 5, 10, 15, 20, 30, 50, 100, 200, 500, 1000, 5000, 10000, or a range consisting of any two of the above values.
[0214] In some embodiments, the glass transition temperature of the aldehyde-ketone polymer is T g4 , its unit is ℃, -100≤T g4 ≤50; optionally, -80≤T g4 ≤30.
[0215] For example, the glass transition temperature of the aldehyde-ketone polymer may be -100°C, -90°C, -80°C, -60°C, -30°C, 0°C, 30°C, 50°C, or a range consisting of any two of the above values.
[0216] In some embodiments, the aldehyde-ketone polymer comprises a structural unit represented by formula (DI),
[0217] In formula (DI), R 41 Including single bonds, substituted or unsubstituted C1-C6 methylene; R 42 including hydrogen atoms, substituted or unsubstituted C1-C6 alkyl groups;
[0218] Optionally, R 41 including single bonds, substituted or unsubstituted C1-C2 methylene groups;
[0219] Optionally, R 42 This includes a hydrogen atom, and a substituted or unsubstituted C1-C3 alkyl group.
[0220] In the embodiments of the present application, a single bond indicates that the group does not exist, and the atoms on both sides of the group are connected by a single bond, for example, R 41 is a single bond, indicating R 41 The carbon atoms on both sides are connected by single bonds.
[0221] Illustratively, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (DI-1) to the structural units represented by formula (DI-6),
[0222] Illustratively, the aldehyde-ketone polymer includes a structural unit represented by formula (DII),
[0223] In formula (DII), R 43 to R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from an integer from 0 to 5, and at least one of r and s is selected from a positive integer; optionally, R 43 to R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C2 hydroxyalkyl group, or a substituted or unsubstituted C1-C2 alkoxy group.
[0224] In some embodiments, the aldehyde-ketone polymer includes at least one of the structural units represented by formula (DII-1) to the structural units represented by formula (DII-4),
[0225] The molecular chain entanglement degree of the above-mentioned aldehyde-ketone polymer is low, which is conducive to improving the flexibility of the molecular chain. The molecular chain can fully stretch in the electrolyte, which is conducive to forming a gel-state substance with the electrolyte.
[0226] The above polymers are only examples of the structural groups of the main molecular chain. In the embodiments of the present application, the polymers can also be obtained by copolymerizing the above structural groups with other types of structural groups (such as olefin structural units, enol structural units, acrylonitrile structural units, etc.).
[0227] When the above-mentioned groups are substituted, the substituents may include one or more of a nitrile group (-CN), a nitro group, a sulfonyl group, a carboxyl group, an ester group, a chlorine atom, a fluorine atom, and a bromine atom. These substituents are high-pressure-resistant substituents and are more conducive to stabilizing the structure of the polymer.
[0228] In some embodiments, n is a positive integer selected from 500 to 15,000.
[0229] Optionally, n is selected from a positive integer between 500 and 10,000.
[0230] In some embodiments, the molecular weight of the polymer is 1.2×10 5 g / mol to 1.0×10 6 g / mol.
[0231] For example, the molecular weight of the polymer may be 1.2×10 5 g / mol, 2×10 5 g / mol, 5×10 5 g / mol, 8×10 5 g / mol, 1×10 6 g / mol, 1.0×10 6 g / mol or a range consisting of any two of the above values.
[0232] The above-mentioned polymers are only examples of the structural groups of the main molecular chains. In the embodiments of the present application, the polymers can also be obtained by copolymerizing the above-mentioned structural groups with a small amount of other types of structural groups (such as olefin structural units, ester monomers, nitrile monomers, amide monomers and other structural units).
[0233] In the embodiments of the present application, when the lyophilic polymer further satisfies one or more of the following conditions, the reliability and cycle performance of the battery cell can be further improved.
[0234] In some embodiments, the lyophilic polymer is added to a first solvent at 70°C to form a polymer system. The polymer system is then allowed to stand for 8 hours at 70°C and for ≥24 hours at 25°C. After these two stages of standing, the polymer system partially swells and adsorbs to form a gel-like substance. The polymer system is then filtered through a 200-mesh filter, leaving the first substance. The mass of the lyophilic polymer is n, expressed in g; the mass of the first substance is m, expressed in g. The polymer and the first substance satisfy the following conditions: 5 ≤ m / n ≤ 1000; alternatively, 10 ≤ m / n ≤ 1000; further alternatively, 10 ≤ m / n ≤ 50. For example, m / n can be 5, 10, 20, 25, 28, 30, 32, 35, 40, 50, 80, 100, 200, 500, 1000, or a range consisting of any two of these values.
[0235] Illustratively, based on the mass of the polymer system, the ratio of the mass content of the lyophilic polymer to the mass content of the first solvent ranges from 1:100 to 1:10, for example, 3:50.
[0236] Exemplarily, the first solvent is the same as or similar to the solvent of the electrolyte, and the first solvent may include a carbonate solvent, for example, a carbonate solvent including a cyclic carbonate solvent and / or a linear carbonate solvent.
[0237] As examples of the cyclic carbonate solvent, the cyclic carbonate solvent includes one or more of ethylene carbonate EC, vinylene carbonate VC, fluoroethylene carbonate FEC, difluoroethylene carbonate DFEC, vinyl ethylene carbonate VEC, and dioctyl carbonate CC.
[0238] As examples of the linear carbonate solvent, the linear carbonate solvent includes one or more of dimethyl carbonate DMC, diethyl carbonate DEC, ethyl methyl carbonate EMC, diphenyl carbonate DPC, methyl allyl carbonate MAC, and polycarbonate VA.
[0239] Optionally, the first solvent may also contain a lithium salt and an electrolyte additive, such as lithium hexafluorophosphate, vinylene carbonate VC, fluorovinylene carbonate FEC, and the like.
[0240] In this application, m / n is also referred to as the precipitation value, which characterizes the ability of the lyophilic polymer and the solvent to transform into a gel-state substance.
[0241] The first substance mainly includes a gel-state substance formed by a lyophilic polymer and a first solvent. In this type of gel-state substance, the molecular structure of the polymer basically does not change.
[0242] In some embodiments, the first substance is dried at 80° C. for 12 hours to remove the first solvent in the first substance. Detection by infrared spectrophotometry IR or nuclear magnetic resonance NMR testing shows that the main component of the first substance after drying is the lyophilic polymer described above.
[0243] The relevant parameters of the lyophilic polymer according to the embodiment of the present application can be detected by the following methods:
[0244] The groups of the lyophilic polymers of the embodiments of the present application can be detected by infrared spectrophotometry IR. Specifically, the lyophilic polymers are tested using a Thermo Nicolet Nexus 670 attenuated total reflectance Fourier transform infrared spectrometer (FTIR-ATR), and then tested in accordance with the standard GB / T6040-2002. The test range is: ATR method 600-4000 cm -1 ; Repeatability: ±2cm -1 ; Resolution: better than 4cm -1 ; Transmission depth 0.2~0.6μm.
[0245] The structure of the lyophilic polymer according to the embodiment of the present application can be tested by nuclear magnetic resonance (NMR). Specifically, 1H NMR and 13C NMR are performed on a Varian Mercury Plus-400 NMR spectrometer at a test temperature of 20° C., TMS as an internal standard, CDCl 3 as a solvent, and a proton resonance frequency of 400 MHz.
[0246] The polymer monomer type of the lyophilic polymer in the embodiment of the present application (especially suitable for monomers with a relatively small proportion in the polymer) can be tested by pyrolysis-gas chromatography-mass spectrometry. The specific testing steps are as follows: accurately weigh 0.5 mg of sample and put it into the sample cup. After fixing it to the injection rod, it is loaded into the pyrolyzer installed near the GC (gas chromatography) injection port. After the pyrolyzer temperature reaches the set temperature, press the injection button, and the sample cup falls rapidly into the core of the pyrolysis furnace by free fall. In the inert gas N2 atmosphere, the volatile components are instantly vaporized and carried into the gas chromatography column by the carrier gas for separation. Finally, it is detected by a flame ionization detector FID or a mass spectrometer MS to obtain a gas chromatogram or a total ion current diagram.
[0247] The molecular weight of the lyophilic polymer in the embodiment of the present application has a well-known meaning in the art and can be measured using commonly used equipment and methods in the art. Gel permeation chromatography (GPC) testing can be used. The specific testing steps are as follows: take an appropriate amount of the sample to be tested (the sample concentration is sufficient to ensure 8%-12% shading), add 20 ml of deionized water, and simultaneously supercharge for 5 minutes (53 KHz / 120 W) to ensure that the sample is completely dispersed, and then measure the sample in accordance with GB / T19077-2016 / ISO 13320:2009 standard.
[0248] Alternatively, a multi-angle laser light scattering (MALLS) instrument was used for testing. Specifically, a GPC coupled with a Dawn Heleos II multi-angle laser light scattering device, an Optilab T-rEX refractive index (RI) detector, and a Visco Star II viscometer (Wyatt Technology Corporation, USA) was used. Testing was conducted at 30°C, using tetrahydrofuran as the mobile phase at a flow rate of 1.0 ml / min. SEC-SAMLL data were processed using the commercial ASTRA6 software to obtain molecular weight parameters.
[0249] [Positive electrode]
[0250] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material and a lyophilic polymer.
[0251] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on either or both of the two facing surfaces of the positive electrode current collector.
[0252] The positive electrode active material layer includes a positive electrode active material, which can be a positive electrode active material commonly known in the art for use in battery cells. For example, the positive electrode active material can include at least one of the following materials: a lithium-containing phosphate compound, a lithium-containing transition metal oxide, a sodium-containing phosphate compound, and a sodium-containing transition metal oxide.
[0253] For example, the general formula of the olivine-type phosphate active material (lithium-containing phosphate compound) is: Li x A y Me a M b P 1-c X c Y z, wherein 0≤x≤1.3, 0≤y≤1.3, and 0.9≤x+y≤1.3; 0.9≤a≤1.5, 0≤b≤0.5, and 0.9≤a+b≤1.5; 0≤c≤0.5; 3≤z≤5; A includes one or more of Na, K, and Mg; Me includes one or more of Mn, Fe, Co, and Ni; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; X includes one or more of S, Si, Cl, B, C, and N; and Y includes one or more of O and F. Specifically, the olivine-type phosphate active material includes one or more of LiFePO4, LiMnPO4, LiNiPO4, and LiCoPO4.
[0254] For example, lithium transition metal oxides (layered materials such as ternary, lithium nickelate / sodium, lithium cobaltate / sodium, lithium manganate / sodium, lithium-rich layered and rock salt phase layered materials). The general formula of the layered structure positive electrode active material is: Li x A y Ni a Co b Mn c M (1-a-b-c) Y z , wherein 0≤x≤2.1, 0≤y≤2.1, and 0.9≤x+y≤2.1; 0≤a≤1, 0≤b≤1, 0≤c≤1, and 0.1≤a+b+c≤1; 1.8≤z≤3.5; A includes one or more of Na, K, and Mg; M includes one or more of B, Mg, Al, Si, P, S, Ca, Sc, Ti, V, Cr, Fe, Cu, Zn, Sr, Y, Zr, Nb, Mo, Cd, Sn, Sb, Te, Ba, Ta, W, Yb, La, and Ce; Y includes one or more of O and F. Optionally, y=0. Specifically, the layered structure positive electrode active material may include lithium cobalt oxide LCO, lithium nickel oxide LNO, lithium manganese oxide LMO, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523),LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622),LiNi 0.8 Co 0.1 Mn 0.1 One or more of O2 (NCM811) and NCA.
[0255] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil or an aluminum alloy foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include a combination of one or more selected from aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. The polymer material base layer may include a combination of one or more selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0256] In some embodiments, the positive electrode active material layer may further optionally include a positive electrode conductive agent. The present application does not particularly limit the type of positive electrode conductive agent. For example, the positive electrode conductive agent may include a combination of one or more selected from superconducting carbon, conductive carbon black, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the positive electrode conductive agent is less than 5% based on the total mass of the positive electrode active material layer.
[0257] In some embodiments, the positive electrode active material layer may also optionally include a positive electrode binder. The embodiments of the present application do not particularly limit the type of positive electrode binder. As an example, the positive electrode binder may include a combination of one or more selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylic resin. In some embodiments, based on the total mass of the positive electrode active material layer, the mass percentage of the positive electrode binder is less than 5%. Compared to the crystallinity of the fluoropolymer of the embodiment of the present application, the crystallinity of the positive electrode binder is higher. Compared to the melting temperature of the fluoropolymer of the embodiment of the present application, the melting temperature of the positive electrode binder is higher.
[0258] The positive electrode active material layer is typically formed by coating the positive electrode slurry onto the positive electrode current collector, drying, and cold pressing. The positive electrode slurry is typically formed by dispersing the positive electrode active material, lyophilic polymer, optional conductive agent, optional binder, and any other components in a solvent and stirring them uniformly. The solvent can be, but is not limited to, N-methylpyrrolidone (NMP). Of course, the preparation of the positive electrode sheet is not limited to the above method; the preparation methods described above can also be used.
[0259] [Negative electrode]
[0260] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector and comprising a negative electrode active material. For example, the negative electrode current collector has two surfaces that oppose each other in its thickness direction, and the negative electrode active material layer is disposed on either or both of the two opposing surfaces of the negative electrode current collector.
[0261] The negative electrode active material can be any negative electrode active material known in the art for use in battery cells. For example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, a silicon-carbon composite, a silicon-nitrogen composite, and a silicon alloy. The tin-based material may include at least one of elemental tin, tin oxide, and a tin alloy.
[0262] In some embodiments, the negative electrode active material layer may further optionally include a negative electrode conductive agent. The present embodiments do not particularly limit the type of the negative electrode conductive agent. For example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is ≤5% based on the total mass of the negative electrode active material layer.
[0263] In some embodiments, the negative electrode active material layer may further optionally include a negative electrode binder. The present application embodiment does not particularly limit the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder based on the total mass of the negative electrode active material layer is ≤5%.
[0264] In some embodiments, the negative electrode active material layer may optionally include other additives. For example, these additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like. In some embodiments, the weight percentage of these other additives is ≤ 2% based on the total weight of the negative electrode active material layer.
[0265] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, a copper alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0266] The negative electrode active material layer is typically formed by coating a negative electrode slurry onto a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is typically formed by dispersing the negative electrode active material, a lyophilic polymer, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water. Of course, the preparation of the negative electrode sheet is not limited to the above method; the preparation method described above may also be used.
[0267] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode active material layer. For example, in some embodiments, the negative electrode plate described herein further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode active material layer and disposed on the surface of the negative electrode current collector. In other embodiments, the negative electrode plate described herein further includes a protective layer covering the surface of the negative electrode active material layer.
[0268] [Isolation film]
[0269] The isolation film includes a substrate and a coating layer disposed on at least one surface of the substrate.
[0270] As some examples, the substrate is generally a porous structure having pores, and the lyophilic polymer may be distributed in the pores of the substrate.
[0271] As other examples, the lyophilic polymer may be distributed within the coating.
[0272] As yet some further examples, the lyophilic polymer may be disposed on a surface of the coating layer facing away from the substrate.
[0273] The specific distribution position of the lyophilic polymer can be any one of the above three forms, any two of them, or a combination of the above three positions.
[0274] The embodiments of the present application do not particularly limit the material of the substrate. Any known substrate with good chemical and mechanical stability can be selected, such as at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The substrate can be a single-layer film or a multi-layer composite film. When the substrate is a multi-layer composite film, the materials of each layer can be the same or different. The substrate is typically a porous structure having pores, and the lyophilic polymer can be distributed in the pores of the substrate.
[0275] In some embodiments, the coating layer may further include a filler. Further, the filler may include at least one of inorganic particles and organic particles. The lyophilic polymer may be distributed in the coating layer.
[0276] In some embodiments, a lyophilic polymer may be disposed on a surface of the coating facing away from the substrate.
[0277] In some embodiments, the decomposition temperature of the filler may be above 200° C., so that the filler has good thermal stability and is not easily decomposed, thereby further improving the heat resistance of the isolation membrane.
[0278] The inorganic particles have the characteristics of high thermal stability and non-decomposability. Optionally, the inorganic particles include at least one of inorganic particles with a dielectric constant of 5 or greater, inorganic particles with ion conductivity but not storing ions, and inorganic particles capable of undergoing electrochemical reactions.
[0279] Optionally, the inorganic particles having a dielectric constant of 5 or more include boehmite, aluminum oxide, zinc oxide, silicon oxide, titanium oxide, zirconium oxide, barium oxide, calcium oxide, magnesium oxide, nickel oxide, tin oxide, cerium oxide, yttrium oxide, hafnium oxide, aluminum hydroxide, magnesium hydroxide, silicon carbide, boron carbide, aluminum nitride, silicon nitride, boron nitride, magnesium fluoride, calcium fluoride, barium fluoride, barium sulfate, magnesium aluminum silicate, lithium magnesium silicate, sodium magnesium silicate, bentonite, hectorite, zirconium titanate, barium titanate, Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviated as PLZT, 0<m<1, 0<n<1), Pb(Mg3Nb 2 / 3)O3-PbTiO3 (abbreviated as PMN-PT), and at least one of their respective modified inorganic particles. Optionally, the modification method of each inorganic particle may be chemical modification and / or physical modification. The chemical modification method includes coupling agent modification (for example, using silane coupling agent, titanate coupling agent, etc.), surfactant modification, polymer grafting modification, etc. The physical modification method may be mechanical force dispersion, ultrasonic dispersion, high energy treatment, etc. The modification treatment can reduce the agglomeration of inorganic particles, thereby enabling them to form a more stable and uniform spatial network structure with nanocellulose; in addition, by selecting coupling agents, surfactants or polymer-modified inorganic particles with specific functional groups, it is also helpful to improve the coating's wetting properties for the electrolyte and improve the bonding strength between the coating and the substrate.
[0280] Optionally, the inorganic particles having ion conductivity but not storing ions include Li3PO4, lithium titanium phosphate Li x1 Ti y1 (PO4)3, lithium aluminum titanium phosphate Li x2 Al y2 Ti z1 (PO4)3, (LiAlTiP) x3 O y3 Type glass, lanthanum lithium titanate Li x4 La y4 TiO3, lithium germanium thiophosphate Li x5 Ge y5 P z2 S w , lithium nitride Li x6 N y6 、SiS2 type glass Li x7 Si y7 S z3 and P2S5 glass Li x8 P y8 S z4 At least one of the following: 0<x1<2, 0<y1<3, 0<x2<2, 0<y2<1, 0<z1<3, 0<x3<4, 0<y3<13, 0<x4<2, 0<y4<3, 0<x5<4, 0<y5<1, 0<z2<1, 0<w<5, 0<x6<4, 0<y6<2, 0<x7<3, 0<y7<2, 0<z3<4, 0<x8<3, 0<y8<3, 0<z4<7. This can further improve the ion transport properties of the isolation membrane.
[0281] Organic particles have good thermal stability and are not easy to decompose, which can improve the heat resistance of the isolation membrane; at the same time, when the internal temperature of the battery cell reaches the melting point of the organic particles due to overcharge abuse, heat abuse, etc., the organic particles can also melt and be absorbed into the micropores of the substrate due to capillary action to play a role in closing the pores and breaking the circuit, which is beneficial to ensure that the battery cell has high safety performance.
[0282] In some embodiments, the organic particles include but are not limited to at least one of polyethylene particles, polypropylene particles, polystyrene particles, melamine resin particles, phenolic resin particles, polyester particles (e.g., polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate), polyimide particles, polyamideimide particles, polyaramid particles, polyphenylene sulfide particles, polysulfone particles, polyethersulfone particles, polyetheretherketone particles, polyaryletherketone particles, and copolymers of butyl acrylate and ethyl methacrylate (e.g., cross-linked polymers of butyl acrylate and ethyl methacrylate).
[0283] In some embodiments, the coating further comprises a binder. The present application does not particularly limit the type of binder; any known material with good adhesive properties may be used. For example, the binder comprises at least one of an aqueous solution-based acrylic resin (e.g., a homopolymer of acrylic acid, methacrylic acid, or sodium acrylate, or a copolymer with other comonomers), polyvinyl alcohol, an isobutylene-maleic anhydride copolymer, and polyacrylamide.
[0284] Optionally, the content of the binder in the coating is less than 30%, based on the mass of the coating.
[0285] [Electrolyte]
[0286] During the charge and discharge process of a battery cell, active ions are embedded and released back and forth between the positive and negative electrodes, and the electrolyte conducts the active ions between the positive and negative electrodes. This application does not specifically limit the type of electrolyte, and it can be selected according to actual needs.
[0287] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not particularly limited and can be selected according to actual needs.
[0288] When the battery cell of the present application is a lithium-ion battery, as an example, the electrolyte salt may include but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0289] When the battery cell of the present application is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalatophosphate) (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).
[0290] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0291] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.
[0292] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly through a winding process and / or a lamination process.
[0293] In some embodiments, the battery cell may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0294] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0295] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process or a lamination process.
[0296] The present application has no particular limitation on the shape of the battery cell, which can be cylindrical, square or any other shape. FIG1 shows a battery cell 5 of a square structure as an example.
[0297] In some embodiments, as shown in Figures 1 and 2, the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.
[0298] The manufacturing method of the battery cell of the present application is well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, separator, and negative electrode sheet can be wound or laminated to form an electrode assembly. The electrode assembly is then placed in an outer packaging, dried, and then injected with electrolyte. The battery cell is then vacuum packaged, allowed to stand, formed, and shaped to obtain a battery cell.
[0299] In some embodiments of the present application, the battery cells according to the present application can be assembled into a battery module. The battery module can contain multiple battery cells, and the specific number can be adjusted according to the application and capacity of the battery module.
[0300] Figure 3 is a schematic diagram of an exemplary battery module 4. As shown in Figure 3 , within the battery module 4, multiple battery cells 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple battery cells 5 may be secured together using fasteners.
[0301] Optionally, the battery module 4 may further include a housing having an accommodation space, and the plurality of battery cells 5 are accommodated in the accommodation space.
[0302] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0303] Both the battery module 4 and the battery pack can be used as specific examples of batteries in the embodiments of the present application.
[0304] Figures 4 and 5 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 4 and 5, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0305] Electrical devices
[0306] In a second aspect, the present application provides an electrical device, which includes at least one of the battery cells, battery modules and battery packs of the present application. The battery cells, battery modules and battery packs can be used as power sources for the electrical device, and can also be used as energy storage units for the electrical device. The electrical device may be, but is not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc. In some embodiments, the battery cell includes an injection hole for injecting electrolyte; when the battery cell is applied to the electrical device, the injection hole is located at the bottom of the battery cell in the vertical direction. Since the amount of free electrolyte in the battery cell is extremely small, or even no free electrolyte, when the injection hole is set at the bottom of the battery cell in the vertical direction, the reliability of the battery cell can also be improved, thereby improving the reliability of the electrical device.
[0307] The electric device can select a battery cell, battery module or battery pack according to its usage requirements. Figure 6 is a schematic diagram of an electric device as an example. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the high power and high energy density requirements of the electric device, a battery pack 1 or a battery module can be used. As another example, the electric device can be a mobile phone, a tablet computer, a laptop computer, etc. The electric device usually requires to be lightweight and thin, and a battery cell can be used as a power source.
[0308] Example
[0309] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0310] Example 1 Preparation of lithium-ion battery
[0311] (1) Preparation of positive electrode sheet:
[0312] Aluminum foil with a thickness of 12 μm was used as the positive electrode current collector.
[0313] The lyophilic polymer and the positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2 O2 (NCM622), conductive carbon black, and binder polyvinylidene fluoride (PVDF) are added to N-methylpyrrolidone (NMP) and mixed to create the positive electrode slurry. The mass ratio of the lyophilic polymer, NCM622, conductive carbon black, PVDF, and N-methylpyrrolidone (NMP) in the positive electrode slurry is 0.5:96.8:2.2:0.5. The positive electrode slurry is coated on the current collector aluminum foil and dried at 85°C before cold pressing. After trimming, cutting, and slitting, the positive electrode sheets are then dried under vacuum at 85°C for 4 hours to form the positive electrode sheets.
[0314] (2) Preparation of negative electrode sheet:
[0315] A copper foil with a thickness of 8 μm was used as the negative electrode current collector.
[0316] The negative electrode slurry was prepared by adding a lyophilic polymer, artificial graphite (the negative electrode active material), carbon black (the conductive agent), styrene-butadiene rubber (SBR) (the binder), and sodium carboxymethyl cellulose (CMC) (the thickener) to water in a weight ratio of 2.5:94.9:2:0.5:0.1 and mixing them evenly. The negative electrode slurry was then coated onto the current collector copper foil and dried at 85°C. The negative electrode sheet was then cold-pressed, trimmed, cut, and slit, and then dried at 120°C under vacuum for 12 hours.
[0317] (3) Preparation of electrolyte:
[0318] In an environment with a water content of less than 10ppm, the non-aqueous organic solvents ethylene carbonate EC and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 3:7 to obtain an electrolyte solvent. Subsequently, the lithium salt LiPF6 and the mixed solvent are mixed to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0319] (4) Preparation of lithium-ion batteries:
[0320] A 16 μm polyethylene film (PE) is used as the substrate of the isolation membrane, and a polymer coating is coated on the surface of the substrate. The mass contents of conventional vinylidene fluoride (PVDF) and binder styrene butadiene rubber (SBR) in the polymer coating are 85%:15% respectively.
[0321] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive electrode sheet and the negative electrode sheet to serve as an isolation, and then wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, dried, and then injected with electrolyte, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0322] Comparative Example 1
[0323] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that no lyophilic polymer was added to the positive electrode slurry of Comparative Example 1, and no lyophilic polymer was added to the negative electrode slurry.
[0324] Example 2-1 to Example 2-4
[0325] Lithium-ion batteries were prepared using a method similar to that of Example 1. The difference from Example 1 was that the amount of the lyophilic polymer added to the negative electrode slurry was adjusted in Examples 2-1 to 2-4.
[0326] Example 3-1 to Example 3-4
[0327] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the amount of injected electrolyte was adjusted in Examples 3-1 and 3-4.
[0328] Example 4-1 to Example 4-4
[0329] A lithium-ion battery was prepared using a method similar to that of Example 1. The difference from Example 1 was that the type of lyophilic polymer was adjusted in Examples 4-1 and 4-4.
[0330] Example 5-1 to Example 5-3
[0331] A lithium-ion battery was prepared using a method similar to that of Example 1. Unlike Example 1, the setting position of the lyophilic polymer was adjusted in Examples 5-1 to 5-3. In Example 5-3, the mass content of polycarbosilane PCS was 80%, the mass content of the lyophilic polymer was 10%, and the mass content of the binder was 10%.
[0332] The data of the examples and comparative examples are shown in Table 1.
[0333] Test section
[0334] 1. Lithium-ion battery cycle performance test
[0335] The lithium-ion batteries prepared in the examples and comparative examples were charged and discharged at a rate of 1C at 25±2°C for a full charge-discharge cycle test until the capacity of the secondary battery decayed to 80% of the initial capacity. The test was then stopped and the number of cycles was recorded.
[0336] 2. Lithium-ion battery module vibration test
[0337] The lithium-ion batteries prepared in the examples and comparative examples were charged to 100% SOC at 0.5C (i.e., a current of 0.5 times the capacity rate) at 25±2°C and left to stand for 1 hour. A small hole with a diameter of 2mm was drilled at the bottom of the battery cell to simulate the battery cell leakage scenario. 12 battery cells were connected in series to form a group, one end of the module was connected to the negative electrode of the module, and the other end was half-lapped / lapped to the end plate. An external voltage of 200V was applied and observed for 1 hour (if a fire occurs, the short-circuit machine can be disconnected) to confirm whether there is an insulation failure fire and the time of the fire.
[0338] Table 1
[0339] In Table 1, VDF stands for vinylidene fluoride, HFP stands for hexafluoropropylene, and TFE stands for tetrafluoroethylene. 80% VDF + 15% HFP + 5% TFE means that, based on the total weight of all monomers, the weight percentages of VDF are 80%, HFP are 15%, and TFE are 5%.
[0340] The nominal capacity x of the batteries of the comparative example and the example is 151 Ah.
[0341] Table 2
[0342] It can be seen from Tables 1 and 2 that the positive and negative electrode sheets of Comparative Example 1 do not contain a lyophilic polymer. During the cycle of the lithium-ion battery, due to the volume change of the lithium-ion battery, the electrolyte in the electrode assembly may be squeezed out, causing a liquid shortage problem, thereby increasing the risk of lithium dendrites and deteriorating the reliability and cycle performance of the lithium-ion battery.
[0343] In the embodiment of the present application, a lyophilic polymer is added to at least one of the positive electrode sheet, the negative electrode sheet and the isolation membrane. The lyophilic polymer can form a condensed electrolyte with the electrolyte, thereby improving the liquid retention capacity, thereby improving the reliability and cycle performance of the lithium-ion battery.
[0344] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and components may be substituted with equivalents without departing from the scope of the present application. In particular, the various technical features described in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but encompasses all technical solutions within the scope of the claims.
Claims
1. A battery cell, comprising an electrode assembly and an electrolyte, wherein the electrode assembly comprises a first pole piece, a second pole piece and a separator, wherein the first pole piece and the second pole piece have opposite polarities, the separator is disposed between the first pole piece and the second pole piece, and at least one of the first pole piece, the second pole piece and the separator comprises a lyophilic polymer; the battery cell satisfies the following formula: y represents the mass of free electrolyte in the battery cell, in g; M represents the mass of the battery cell before drying, and its unit is g; M' represents the mass of the battery cell after drying, and its unit is g.
2. The battery cell according to claim 1, wherein: Optionally, 3. The battery cell according to claim 1 or 2, wherein: The battery cell also satisfies the following formula: and / or m1 represents the mass of the electrode assembly before drying, and its unit is g; m2 represents the mass of the electrode assembly after drying, and its unit is g.
4. The battery cell according to any one of claims 1 to 3, wherein: The amount of free electrolyte per unit capacity of the battery cell is b, the unit of which is mg / Ah, 0≤b≤1400; Optionally, 0.1≤b≤1000; further optionally, 0.3≤b≤800.
5. The battery cell according to any one of claims 1 to 4, wherein: The first pole piece includes a current collector and an active material layer disposed on at least one surface of the current collector, wherein the active material layer includes the lyophilic polymer and active material particles; The lyophilic polymer is distributed on the surface of the active substance particles; and / or There are a plurality of active material particles, and there is a gap between two adjacent active material particles. The lyophilic polymer is distributed in the gap between the active material particles.
6. The battery cell according to any one of claims 1 to 5, wherein: The isolation film includes a substrate and a coating disposed on at least one surface of the substrate; The lyophilic polymer is distributed in the pores of the substrate; and / or The lyophilic polymer is distributed in the coating; and / or The lyophilic polymer is disposed on the surface of the coating layer facing away from the substrate.
7. The battery cell according to any one of claims 1 to 6, wherein: The lyophilic polymer comprises a fluorinated polymer; The crystallinity of the fluorinated polymer measured by differential scanning calorimetry is Xc1, 0<Xc1≤30%; The melting temperature of the fluorinated polymer is T m1 , its unit is ℃, 0<T m1 ≤140.
8. The battery cell according to claim 7, wherein: The glass transition temperature of the fluorinated polymer is T g1 , the unit is ℃, -150≤T g1 ≤60.
9. The battery cell according to claim 7 or 8, wherein: The fluorinated polymer comprises at least one of the structural units represented by formula (AI) to the structural units represented by formula (AIII), In formula (AI) and formula (AII), R 11 , R 12 , R 13 and R 14 Each independently includes a hydrogen atom, a fluorine atom, a chlorine atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group, and R 11 , R 12 , R 13 and R 14 At least one of the two radicals contains a fluorine atom; when substituted, the substituent includes one or more of a nitrile group (-CN), a nitro group, a sulfonic acid group, a sulfonyl group, an amide group, a carboxyl group, an ester group, and a halogen atom; In formula (AIII), R 15 Including single bonds, substituted or unsubstituted C1-C3 alkyl groups; when substituted, the substituents include one or more of nitrile groups (-CN), nitro groups, sulfonic acid groups, sulfonyl groups, amide groups, carboxyl groups, ester groups, and halogen atoms; p is selected from positive integers from 1 to 3; n is selected from positive integers from 1000 to 30000.
10. The battery cell according to any one of claims 1 to 9, wherein: The lyophilic polymer further comprises an ether polymer, wherein the ether polymer is made into a sheet structure; the sheet structure is m2 The elastic modulus G'-energy loss modulus G" curve is obtained by dynamic frequency scanning test at 20 ° C. The slope of the elastic modulus G'-energy loss modulus G" curve is K1, 1<K1<∞, T m2 ℃ represents the melting temperature of the ether polymer; optionally, 1<K1≤100; further optionally, 1<K1≤10.
11. The battery cell according to claim 10, wherein: The ether polymer comprises a structural unit represented by formula (BI) and / or a structural unit represented by formula (BII), In formula (BI), R 21 and R 22 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; R 23 Including substituted or unsubstituted C1-C5 alkylene; In formula (BII), R 24 To R 27 Each independently includes a hydrogen atom, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 alkoxy group or an ether group, and R 24 To R 27 At least one of them contains a substituted or unsubstituted C1-C3 alkoxy group or an ether group.
12. The battery cell according to any one of claims 1 to 11, wherein: The lyophilic polymer comprises an ester polymer, wherein the ester polymer is made into a sheet-like structure; the sheet-like structure is m3 The elastic modulus G'-energy loss modulus G" curve was obtained by dynamic frequency scanning test at 20 °C. The slope of the elastic modulus G'-energy loss modulus G" curve is K2, 1<K2<∞, T m3 ℃ represents the melting temperature of the ester polymer; optionally, 1<K2≤100; further optionally, 1<K2≤10.
13. The battery cell according to claim 12, wherein: The ester polymer comprises a structural unit represented by formula (CI) and / or a structural unit represented by formula (CII), In formula (CI), R 31 , R 32 and R 33 Each independently includes a hydrogen atom, or a substituted or unsubstituted C1-C8 alkyl group; R 34 Including substituted or unsubstituted C1-C8 alkyl, or substituted or unsubstituted C1-C8 hydroxyalkyl; In formula (CII), R 35 including substituted or unsubstituted C2-C6 methylene; optionally, R 35 Each independently includes a substituted or unsubstituted C2-C4 methylene group.
14. The battery cell according to any one of claims 1 to 13, wherein: The lyophilic polymer comprises an aldehyde-ketone polymer, wherein the aldehyde-ketone polymer is made into a sheet-like structure; the sheet-like structure is m4 The elastic modulus G'-energy loss modulus G" curve is obtained by dynamic frequency scanning test at 20 ° C. The slope of the elastic modulus G'-energy loss modulus G" curve is K3, 0.8≤K3<∞, T m4 ℃ represents the melting temperature of the aldehyde-ketone polymer; optionally, 0.8≤K3≤100; further optionally, 0.8≤K3≤10.
15. The battery cell according to claim 14, wherein: The aldehyde-ketone polymer comprises a structural unit represented by formula (DI) and / or a structural unit represented by formula (DII), In formula (DI), R 41 Including single bonds, substituted or unsubstituted C1-C6 methylene; R 42 Including hydrogen atom, substituted or unsubstituted C1-C6 alkyl; In formula (DII), R 43 To R 46 Each independently includes a hydrogen atom, a hydroxyl group, a substituted or unsubstituted C1-C3 alkyl group, a substituted or unsubstituted C1-C3 hydroxyalkyl group, or a substituted or unsubstituted C1-C3 alkoxy group; r and s are each independently selected from an integer from 0 to 5, and at least one of r and s is selected from a positive integer.
16. The battery cell according to any one of claims 1 to 15, wherein: The molecular weight of the lyophilic polymer is 1.2×10 5 g / mol to 1×10 6 g / mol. 17 . A battery comprising the battery cell according to claim 1 .
18. An electrical device comprising the battery according to claim 17.